New Device for the Treatment of Functional Ischemic Mitral Regurgitation: Proof of Concept in an In Vitro Model - Stock, Sina; Scharfschwerdt, Michael; Warnecke, Rebecca Janina; Richardt, Doreen; Tsvelodub, Stanislav; Sievers, Hans-Hinrich (The Thoracic and Cardiovascular Surgeon, 2019)
Background Optimal surgical treatment of functional ischemic mitral regurgitation (FIMR) is still controversy. Due to the underlying pathophysiology, stand-alone ring annuloplasty is assumed with a high recurrence rate of mitral regurgitation, thus additional subvalvular repair techniques might improve the results. This in vitro study introduces a new device for subvalvular mitral valve repair.Methods We developed a new device for subvalvular mitral valve repair, consisting of two frames for papillary muscle (PM) attachment, which are connected with two holding bars serving for fixation of the device on an annuloplasty ring. In the first experimental run, porcine mitral valves including the chordae tendineae and PMs were fixated on a holding device, consisting of a holding ring simulating mitral annulus dilation and height-adjustable frames for PM attachment simulating leaflet tethering. In vitro regurgitant volume was determined in a pulse duplicator. Afterward, the frames for PM attachment were replaced by our newly developed device and the measurements were repeated.Results In the model simulating FIMR, the regurgitant volume was 44.3 ± 12.38 mL/stroke. After subvalvular reconstruction with our new device, the regurgitant volume was significantly reduced to 33.1 ± 11.68 mL/stroke (p = 0.009).Conclusion In this specific in vitro model, our new device for subvalvular mitral valve reconstruction led to a significant reduction of the regurgitant volume, thus representing a promising technique to potentially improve the results of mitral reconstruction in ischemic functional mitral valve regurgitation. Additional studies are required to further investigate and improve our device.
Keywords: heart valve surgery; mitral valve surgery; ischemic mitral regurgitation; in vitro